2013
DOI: 10.1182/blood.v122.21.926.926
|View full text |Cite
|
Sign up to set email alerts
|

Development Of Second Generation Thiol Isomerase Inhibitors To Prevent Thrombus Formation

Abstract: Protein disulfide isomerase (PDI) is a widely expressed oxidoreductase that catalyzes the rearrangement of intramolecular disulfide bonds during protein maturation in the endoplasmic reticulum. However, PDI can also be secreted from both platelets and endothelial cells during thrombus formation. Inhibition of extracellular PDI in the vasculature using neutralizing antibodies or bacitracin blocks thrombus formation in pre-clinical studies. Our previous experiments identified quercetin-3-rutinoside as an inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The precise mechanisms of this action conferred by ADTM would be another interesting question that is worth investigating in the future. Recently there are accumulating reports that the inhibition of protein disulfide isomerases including PDI and ERp57 could block thrombus formation in various in vivo models and suggest that this protein family represents an important novel class of anti-thrombotic target 39 40 41 42 43 . Preclinical studies demonstrate that deficiency in platelet ERp57 resulted in the increased tail bleeding times and delayed thrombus formation 20 , while PDI is unable to compensate for the absence of platelet ERp57 20 and other study also showed that the blockade of ERp57 with specific antibody further inhibited platelet aggregation in PDI deficient platelets 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanisms of this action conferred by ADTM would be another interesting question that is worth investigating in the future. Recently there are accumulating reports that the inhibition of protein disulfide isomerases including PDI and ERp57 could block thrombus formation in various in vivo models and suggest that this protein family represents an important novel class of anti-thrombotic target 39 40 41 42 43 . Preclinical studies demonstrate that deficiency in platelet ERp57 resulted in the increased tail bleeding times and delayed thrombus formation 20 , while PDI is unable to compensate for the absence of platelet ERp57 20 and other study also showed that the blockade of ERp57 with specific antibody further inhibited platelet aggregation in PDI deficient platelets 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of PDI can affect both platelet aggregation and fibrin generation. Moreover, it is a safe target for the inhibition of thrombus formation ( Flaumenhaft, 2013 ; Kennedy et al, 2013 ). Quercetin-3-rutinoside (rutin) is a kind of flavonoid glycoside, which is abundant in buckwheat, tea, fruits, and berries ( Gullon et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%